Efeitos de uma intervenção educativa por telefone na autoeficácia, duração e exclusividade do aleitamento materno: ensaio clínico randomizado controlado - Chaves, Anne Fayma Lopes (2016)
This study aimed to evaluate the effects of an educational intervention by telephone to improve maternal self-efficacy in breastfeeding, its duration and exclusivity. This is a Randomized Controlled Clinical Trial that compared two groups: Control Group (CG) (routine care) and Intervention Group (IG) (routine care + educational intervention to promote breastfeeding self-efficacy, following the principles of Motivational Interviewing (MI) by phone, with contacts being held 7, 15 and 30 days after delivery). Study conducted in Fortaleza-CE, Brazil, at the Gonzaga Mota District Hospital in Messejana between May and August 2015. At the end, we obtained a sample of 85 nursing mothers at the second month postpartum, with 41 in the IG and 44 in the CG, and 77 nursing mothers at the fourth month postpartum, 39 in IG and 38 in CG. The study was conducted in three phases: 1. Baseline; 2. Intervention; 3. Evaluation of outcomes at second and fourth month postpartum. For data collection in Phase 1, we used the Form for characterization of nursing mothers and the Breastfeeding Self-Efficacy Scale – Short Form (BSES-SF); in Phase 2, for the intervention, we applied a form containing data about the child’s diet and type of items covered in the session. A form was applied to guide the intervention on the MI approach. Furthermore, to implement the MI technique to inform, it was used an instrument based on the 14 items of the BSES-SF and the Serial Album “I can breastfeed my child”; in Phase 3, it was applied a form containing the type of breastfeeding, its duration and exclusivity, along with the BSES-SF. Data were analyzed through the Statistical Package for Social Sciences (SPSS) version 20.0 for Windows. Research Ethics Committee approved the study under protocol No. 1,026,156 and it was registered in the Brazilian Clinical Trials Registry (ReBec) platform. As for the characterization, the groups were similar (p>0.05), except for marital status (p=0.018). In the intergroup self-efficacy evaluation, it was identified that the median scores in the breastfeeding self-efficacy scale were the same at the second month in both groups (p=0.773). Nevertheless, at the fourth month, the IG presented higher levels compared with the CG (p=0.011). In the intergroup evaluation of breastfeeding duration, it was evidenced that the educational intervention was able to maintain significantly breastfeeding until the second month (p=0.035) in the IG, while the CG presented a decrease. In the fourth month, it was also possible to identify that the IG maintained breastfeeding for a longer duration than the CG (p=0.109). With regard to the intergroup evaluation of exclusive breastfeeding, it was noted that the IG and CG presented small differences in exclusivity at the second and fourth months (p=0.983/p=0.573). It was found that women with high education and who breastfed immediately after birth were more likely to breastfeed for a longer period. Additionally, women living with a partner are more likely to practice exclusive breastfeeding at the fourth month. Therefore, data showed that the implementation of educational intervention carried out by nurses via telephone focused on breastfeeding self-efficacy and through motivational interviewing increases the self-efficacy of mothers to breastfeed, as well as the duration of breastfeeding, but does not impact its exclusivity.